Drainage Development in the Dunhuang Basin, NE Tibet, Controlled by Multi-Segment Fault Growth - Chen, Gan; Zheng, Wenjun; Yang, Jingjun; Duan, Lei; Liang, Shumin; Li, Zhigang; Zhang, Dongli; Xiong, Jianguo (Frontiers in Earth Science, 2021)
The Dongbatu Shan (DBTS, also known as the Nanjie Shan), that interrupts the northern Tibetan foreland in the Dunhuang basin is an active anticline. It has accommodated the northwestward growth of the eastern Altyn Tagh fault system (ATF). Although several thrust faults have been identified around the DBTS, their evolution history and influence on regional landscape have received little attention during the late-Quaternary. In this study, several geomorphic methods are used to investigate the interaction between drainage development and tectonic movement around DBTS. Based on high-resolution satellite image, field investigation, and cosmogenic nuclide 10Be dating method, the fluvial landform sequences around DBTS were constructed. Using quantitative geomorphology methods including landscape relief profile, asymmetry factor (AF) and transverse topographic symmetry factor (T), we regard drainage deflection is controlled by multi-segment fault growth. Combined the results of the above-mentioned methods, we propose that Yulin He, flowing across DBTS, had gone through several abandonment since the late mid-Pleistocene due to the lateral propagation of DBTS. Affected by the discharge of channel and multi-segment fault growth, our research confirms that the direction of river abandonment may decoupled with mountain range propagation trend. Based on the chronology dating, the DBTS has gone through two severe uplifts since ~208 ka and the shortening rate across the central DBTS is constrained to be ~1.47 mm/yr since ~83 ka. Given the fact that thrust faults are widely developed around DBTS, we propose that the flower like structure formed by northward growth of the eastern ATF could better explain the development of the secondary subparallel faults.